Learning Accounting Using E-Learning In The Covid-19 Period As An Effort To Improve Student Understanding And Academic Quality: Pembelajaran Akuntansi Menggunakan E-Learning Dimasa Covid-19 Sebagai Upaya Peningkatan Pemahaman Mahasiswa Dan Kualitas Akademik - Winda Afichamala; Wiwit Hariyanto (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine how accounting learning uses e-learning during the Covid-19 period as an effort to increase student understanding and academic quality. The data analysis technique used in this study is to use a form of pattern matching analysis. The results of the research obtained based on data analysis said that the e-learning infrastructure used in UMSIDA, especially the Accounting study program, was good, the e-learning ceiling used in UMSIDA was moodle. In the e-learning learning process at UMSIDA, there are content standards that must be met. Learning accounting using e-learning during the Covid-19 period can be used as an effort to increase student understanding and academic quality, it's just that there needs to be a commitment between students and lecturers.